Accumulation of heavy particles in a circular bounded vortex flow: Parameter influence and comparison. (June 2018) - Ku, Xiaoke; Li, Heng; Lin, Jianzhong; Jin, Hanhui; Shen, Fengli
Highlights: Accumulation of heavy particles in a circular vortex flow has been investigated. Effects of several key operating parameters are systematically explored. Both one-way and two-way couplings are considered and compared with each other. As Stokes number enhances, more particles will accumulate on the wall. The location of the rotating cylinder has a significant impact on the results. Abstract: In this work, the accumulation behavior of heavy particles in a circular bounded viscous vortex flow has been explored by an Euler–Lagrange CFD model. Inter-particle and particle-wall collisions are resolved by a hard-sphere model. Effects of Stokes number, the size and the location of the small rotating cylinder are investigated under both one-way and two-way couplings. Results show that, under one-way coupling, most particles will accumulate at one point inside the domain and the accumulation point will move farther away from the stagnation point of the flow field as Stokes number increases. However, under two-way coupling, there is no accumulation point inside the domain. Instead the majority of particles accumulate on the circular wall. As Stokes number enhances, more particles will accumulate on the wall under both one-way and two-way couplings. The slight change of the rotating cylinder's size has little influence on the results, implying the reliability of using the small rotating cylinder to induce the vortex flow. However, the variation in the rotating cylinder's location has a significant impact on the results. As the small cylinder moves farther away from the center of the circular domain, the accumulation point can extend to an accumulation circle under one-way coupling, and less particles will accumulate on the wall under both one-way and two-way couplings.